Factors Related to The Incidence of Stunting at The Watukawula Puskesmas, Southwest Sumba Regency - Dorce Bulu; Intje Picauly; Amelya B. Sir (Lontar : Journal of Community Health, 2022)
Stunting is still an important health problem to pay attention to. At the Watukawula Puskesmas, the number of stunting toddlers in 2019 was 25,4%, if not addressed, it could have an impact on the growth and development of toddlers. This study aims to determine the factors associated with the incidence of stunting in the working area of ​​ Watukawula Puskesmas. The type of research used is a case-control study design. The sample consisted of 130 children under five consisting of 65 case samples and 65 control samples. The sampling of cases and control samples used a simple random sampling technique. The data analysis used was univariate, bivariate, and multivariate analysis using the chi-square test with a significance level of =0.05. The results showed that knowledge of maternal nutrition (p=0.000), exclusive breastfeeding (p=0.004), history of infectious disease (p=0.001), energy adequacy level (p=0.000), and protein adequacy level (p=0.000) were associated with stunting incidents. Therefore, it is recommended for mothers of toddlers to be able to provide nutritionally balanced food and sufficient energy and protein for their children to achieve optimal child development. Keywords:stunting, knowledge, disease, energy, protein